Pembuatan Beton dengan Campuran Limbah Plastik dan Karakterisasinya - Yessi Rismayasari; Utari U; Usman Santosa (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Research on concrete containing plastic waste as an alternative polymer material has been conducted.It studied the concrete characteristic through compressive strength, impact testing, thermal conductivity, and density testing. Plastic waste used for concrete manufacture was black because it is strong but light. The goal of this research is to determine the characteristics value of concrete with and without plastic waste mixing. Concrete was mixed with the ratio of 1cement: 2 sands: 3 gravel and cement water factor of 0.5. The addition of plastic waste were 0%, 2%, 4%, 6%, 8%, 10% of cement mass.Specimens used was (15x15x15) cm cube with sides for compressive strength testing, (8x2x2) cm a block with the size of for impact testing, acylinder with a diameter of 4cm and thickness respectively 0.2 cm and 0.4 cm for thermal conductivity testing, and a sides (15 x 15 x 15)cm cube with for density testing. The diameter of plastic waste was 0.1 to 0.8 cm. The test was performed at 28 days of concrete age. The result showed that the addition of 4% of plastic waste recorded the best compressive strength, impact testing, and thermal conductivity. In this research, the density was of the range (16 ± 6)x 102 kg / m³up to(22 ± 4) x 102 kg / m³, compressive strength(21.8 ± 0.2) x 106 N / m² of the range (16 ± 0.1) x 106 N / m²to(21.8 ± 0.2) x 106 N / m², impact (8.7 ± 0.3)x 10-1Joule to the range (3.5 ± 0.3)x 10-1Joules up to (8.7 ± 0.3)x 10-1Joule and thermal conductivity (6.0 ± 0.5) x 10 -5 kcal / ms °C was (1.17 ± 0.5) x 10-5 kcal / ms °C to (6.0 ± 0.5) x 10 -5 kcal / ms °C.